2022
DOI: 10.1167/tvst.11.6.18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Paravascular Abnormalities and Choroidal Thickness in Young Highly Myopic Adults

Abstract: Purpose The purpose of this study was to investigate the clinical characteristics of paravascular abnormalities (PVAs) and retinoschisis, and their associations with choroidal thickness (ChT) in young highly myopic (HM) adults. Methods A total number of 645 eyes were included. Paravascular microfolds (PMs), paravascular cystoid spaces (PCs), paravascular lamellar holes (PLHs), and retinoschisis were detected using swept-source optical coherence tomography. Their associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…A higher incidence of PPRS was associated with older age, longer AXL, and the presence of posterior staphyloma [ 44 , 45 , 46 ]. Interestingly, Li et al revealed that the presence of PPRS was negatively associated with the MCT (β = −18.30, p < 0.05) in a recent study that included 645 myopic eyes [ 47 ].…”
Section: Peripapillary Retinoschisis and Holesmentioning
confidence: 99%
“…A higher incidence of PPRS was associated with older age, longer AXL, and the presence of posterior staphyloma [ 44 , 45 , 46 ]. Interestingly, Li et al revealed that the presence of PPRS was negatively associated with the MCT (β = −18.30, p < 0.05) in a recent study that included 645 myopic eyes [ 47 ].…”
Section: Peripapillary Retinoschisis and Holesmentioning
confidence: 99%